Pendampingan Penyusunan Laporan Biaya Produksi Metode Harga Pokok Proses pada UMKM Ikan Kembung Rebus Berkah - Nurhaflah Soraya; Tiara Sabina Nasution (JPM: Jurnal Pengabdian Masyarakat, 2023)
This dedication activity has two objectives, namely (1) to provide an understanding to the partner of Small and Medium Enterprises of boiled mackerel in Deli Serdang Regency regarding the importance of calculating the cost of goods product and formulating it in the form of a production cost report and recording it in the form of a journal, (2) to provide training and assistance to partners so that they are able to calculate the cost of goods product by the cost of good process method correctly. Based on the results of interviews with partners, it can be identified that the problem faced by partners is the partner want to apply for financing to Bank but do not understand the preparation of production cost reports as required by banks because so far partner has only made estimates in determining the cost of production so that the calculation of production costs is invalid. In addition, partner also used the prevailing market price in determining the cost of production. The solution offered to solve the problem is to provide training and assistance in calculating the cost of goods produced. The activity methods used in this service are (1) lectures to convey the concept of calculating the cost of goods produced and recording journals, (2) demonstrations to provide practical examples of making production cost reports and recording journals, (3) assistance at the location of the research object. Based on the results of the activity evaluation, information on the level of understanding of the participants of the material provided was 86%. Furthermore, the service team also continues to provide assistance for one month.